MODERN TECHNOLOGIES FIGURATIVE ART IN THEIR CLASSES OF USE ADVANTAGES (American Journal of Interdisciplinary Research and Development, 2026)
In my article mainly modern technologies figurative art in their classes of use importance and advantages illuminating given. In particular, digital tools using students creative thinking, aesthetics taste and figurative skills develop opportunities analysis Also, interactive methods, multimedia tools and graphic programs through education process efficiency increase issues seeing Modern technologies based on organization done lessons of the students interest increase, independent work skills formation and future to the profession in orientation important factor to be based on given.